Endoplasmic reticulum homeostasis: a potential target for diabetic nephropathy - Yang, Ming; Liu, Chongbin; Jiang, Na; Liu, Yan; Luo, Shilu; Li, Chenrui; Zhao, Hao; Han, Yachun; Chen, Wei; Li, Li; Xiao, Li; Sun, Lin (Frontiers in Endocrinology, 2023)
The endoplasmic reticulum (ER), as the most vigorous organelle in intracellular metabolism, is involved in physiological processes such as protein and lipid synthesis and calcium ion transport. Recently, abnormal function of ER has also been reported to be involved in the progression of kidney disease especially in diabetic nephropathy (DN). Here, we reviewed the function of ER and summarized the regulation of homeostasis through UPR and ER-phagy. Then, we also reviewed the role of abnormal ER homeostasis in residential renal cells of DN. Finally, part of ER stress activator and inhibitors were also summarized, and discussed the possibility of maintaining ER homeostasis as a potential therapeutic target for DN.